Acehnese Culture-Based Artistic Experimentation in the Creation of the Artwork Imajinisan - Fadhlan, Fadhlan; Guntur; Sunarmi (Mudra Jurnal Seni Budaya, 2025)
In Aceh, ancient gravestones, as well as the peusijuek ritual, are increasingly marginalized by modernization and infrastructural development. However, they contain profound symbolic, spiritual, and aesthetic values that remain underrepresented in visual arts discourse. This study aims to explore how local cultural phenomena, particularly Aceh's ancient gravestones and the peusijuek ritual, can serve as conceptual and visual inspiration in the development of contemporary painting techniques. Employing a qualitative method with hermeneutic and artistic practice approaches, the exploration process was conducted through field observations at gravestone sites, visual technique experiments using rubbing, washing, collage, and the gestural act of reutek as a form of spiritual symbolism. All stages were organized in a tiered structure, visualized through a triangular diagram, illustrating an integrative process from observation to visual affirmation. The results show that creating visual techniques based on local culture can produce an authentic and meaningful visual language, while also serving as a reflective medium on the dynamics of cultural preservation amid modernization. These findings affirm that exploratory documentation of the technique creation process plays a crucial role in shaping visual distinctiveness and strengthening the artist's identity within the landscape of contemporary Indonesian art. The study further suggests that experimental practices grounded in local cultural symbols not only enrich the discourse of contemporary painting but also offer a model for sustainable artistic innovation that bridges tradition and modernity.